Exploring the potential of Carica Papaya Leaf Extract: a perspective on its effectiveness in ameliorating thrombocytopenia in dengue patients - Maliha Khalid; Muhammad Saad Khan; Erum Siddiqui; Aminath Waafira (Infection Ecology & Epidemiology)
Background: Dengue fever (DF) is endemic in Pakistan, posing health risks. Recent flooding in 2022 and strong monsoon rains in 2024 have increased the possibility of an epidemic. It is an infectious disease having potentially severe outcomes including thrombocytopenia.Discussion: Carica Papaya Leaf Extract (CPLE) has emerged as an off-label treatment option, showing promising results in increasing platelet counts and reducing hospital stays. However, a critical assessment of existing research reveals methodological flaws, hindering specific recommendations.Conclusion: This perspective advocates for comprehensive research to evaluate the risks and benefits of CPLE as a potential remedy for thrombocytopenia associated with dengue fever. A robust investigation will inform clinical practice and guide healthcare decisions, contributing to improved patient outcomes in dengue-endemic areas.